Assessment of fatigue thresholds in 50-m all-out swimming - Soares, S.; Fernandes, R. J.; Machado, J. L.; Maia, J. A.; Daly, D. J.; Vilas-Boas, J. P. (International Journal of Sports Physiology and Performance, 2014)
Context: It is essential to determine swimmers` anaerobic potential and better plan training, understanding physiological effects of the fatigue. Purpose: To study changes in the characteristics of the intracyclic velocity variation during an all-out 50-m swim and to observe differences in speed and stroking parameters between these changes. Methods: 28 competitive swimmers performed a 50-m front-crawl all-out test while attached to a speedometer. The velocity-time (v[t]) curve off all stroke cycles was analyzed per individual using a routine that included a wavelet procedure, allowing the determination of the fatigue thresholds that divide effort in time intervals. Results: One or 2 fatigue thresholds were observed at individual level on the v(t) curve. In males, when 1 fatigue threshold was identified, the mean velocity and the stroke index dropped (P < .05) in the second time interval (1.7 ± 0.0 vs 1.6 ± 0.0 m/s and 3.0 ± 0.2 vs 2.8 ± 0.3 m/s, respectively). When 2 fatigue thresholds were identified, the mean velocity of the first time interval was higher than that of the third time interval (P < .05), for both male (1.7 ± 0.0 vs 1.6 ± 0.1 m/s) and female (1.5 ± 0.1 vs 1.3 ± 0.1 m/s) swimmers. Conclusion: One or 2 fatigue thresholds were found in the intracyclic velocity-variation patterns. Concurrently, changes in velocity and stroke parameters were also observed between time intervals. This information could allow coaches to obtain new insights into delaying the degenerative effects of fatigue and maintain stable stroke-cycle characteristics over a 50-m event.